Identificación de agentes bacterianos patógenos en muestras de secreción pulmonar del personal custodio y personas privadas de libertad del Centro de Rehabilitación Social de Loja - Alba Jiménez, Luis Enrique (2014)
Bacterial infections of respiratory casualties are caused by the proliferation and invasion of multiple Gram-positive bacterial, Gram negative and acid fast bacilli at the lower respiratory system, are closely related to health conditions , education , health , food and overcrowding population living in rehabilitation centers . The Social Rehabilitation Center of Loja ( CRSL ) is one of the major prisons in the southern region of Ecuador , has a population of 750 prisoners, 50 guards , 10 people in administrative and 3 at the medical clinic , population large to justify the conduct of this study in relation to capacity, the same as I run on a sample of 48 people who met the inclusion criteria , which were able to investigate the most common pathogenic bacterial flora in the airways low and inform the public about importance should be given to such infections and how to prevent or at least reduce them . Upon completion of the research work was concluded that 48 % of people who collaborated with the study enrolled for some bacterial infectious process at the level of the lower respiratory tract , with the same negative Gram type as Klebsiella pneumoniae 12.5 % , Klebsiella oxytoca , Klebsiella ozaenae , Citrobacter freundii , Proteus vulgaris , Escherichia coli and 4.2 % respectively for the Gram positive bacteria Staphylococcus aureus with 8.3 % and 6.3 % Streptococcus pyogenes , which is important to mention that Mycobacterium tuberculosis ( tubercle bacillus was found). Keywords: Mycobacterium tuberculosis, Enterobacteriaceae, Bacillus Koch, Gram.